2006
DOI: 10.1614/ws-06-014r.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulated insect defoliation and duration of weed interference affected soybean growth

Abstract: An improved understanding of crop stress from multiple pests is needed for better implementation of integrated pest management (IPM) strategies. Field studies were conducted in 2003 and 2004 at two locations in eastern Nebraska to describe the effects of simulated early-season insect defoliation of soybean and duration of weed interference on soybean growth. Three levels of simulated defoliation (undefoliated, 30, and 60%) and seven durations of weed interference (weedy and weed free; weed removal at V2, V4, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…(73) B, the slope of the line at the inflection point; C, the lower limit; I 50 , the growing degree days giving a 50% response between the upper and lower limit (also known as the "inflection point" Other researchers also observed that the CTWR in other crops was not stable among locations, but was highly dependent on the density, competitiveness and emergence periodicity of the weed population present (Evans et al 2003a(Evans et al , 2003b. Our findings are similar to previous reports of the CTWR in other crops, including soybean (Van Acker et al 1993;Knezevic et al 2003;Gustafson et al 2006aGustafson et al , 2006b, maize (Evans et al 2003a(Evans et al , 2003b, carrot (Daucus carota L.) (Swanton et al 2010) and leek (Allium porrum L.) (Tursun et al 2007). …”
Section: Critical Time For Weed Removalsupporting
confidence: 88%
See 2 more Smart Citations
“…(73) B, the slope of the line at the inflection point; C, the lower limit; I 50 , the growing degree days giving a 50% response between the upper and lower limit (also known as the "inflection point" Other researchers also observed that the CTWR in other crops was not stable among locations, but was highly dependent on the density, competitiveness and emergence periodicity of the weed population present (Evans et al 2003a(Evans et al , 2003b. Our findings are similar to previous reports of the CTWR in other crops, including soybean (Van Acker et al 1993;Knezevic et al 2003;Gustafson et al 2006aGustafson et al , 2006b, maize (Evans et al 2003a(Evans et al , 2003b, carrot (Daucus carota L.) (Swanton et al 2010) and leek (Allium porrum L.) (Tursun et al 2007). …”
Section: Critical Time For Weed Removalsupporting
confidence: 88%
“…The CPWC consists of two components. The first is the critical time for weed removal (CTWR), which determines the point in the growing season when weeds must be removed to prevent unacceptable yield losses, and the second is the end of the critical period, which determines the time in crop growth when lateemerging weeds will no longer cause yield loss (Knezevic et al 2002;Gustafson et al 2006b). Determining the CTWR as influenced by pre-emergence (PRE) herbicide application would help producers in optimizing weed control strategies in sunflower, and time their POST weed control applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, plants completely defoliated were more adversely affected by defoliation than those subjected to mild (25 or 50 %) defoliation. According to Gustafson et al (2006), defoliation may cause yield reductions by affecting the photosynthate production and its distribution into various parts of the crop depending on the intensity of defoliation. Plants completely defoliated might have recorded a more drastic reduction of their photosynthetic apparatus as compared to those from mild defoliations.…”
Section: Discussionmentioning
confidence: 99%
“…One-third leaf removal from basal portion of the canopy in cowpea increased grain yield over control and severe defoliation decreased seed yield (Hossain et al 2006, Gustafson et al 2006. Likewise, mild defoliations (16.6 -20%) during reproductive phase did not adversely affect seed yield in soybean (Board and Harvelle 1998) and in mungbean (Pandey andSingh 1984, Begum et al 1997).…”
Section: Introductionmentioning
confidence: 99%